Optimizing the Management of Zakat, Infaq, and Sadaqah for Post-Disaster Economic Recovery Through Local Policy Approaches - Ashabul Fadhli; Rina Susanti; Nike Apriyanti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to examine the mechanism of zakat, infaq, and sadaqah (ZIS) management implemented by the Nagari Sungai Pua Government Institution in the context of post-disaster economic recovery. Natural disasters in Nagari Sungai Pua have caused significant disruptions to the community’s financial stability. Many victims have lost their homes, which also served as places of business and livelihood, in addition to experiencing crop failures and other economic hardships. In response to these conditions, the Nagari Sungai Pua Government Institution has initiated a collective effort to regulate ZIS management through local policies tailored to the community's social context. This research is field-based, utilizing primary data collected through interviews with local government representatives, community leaders, and disaster survivors. The findings indicate that ZIS management in Nagari Sungai Pua is conducted systematically, fulfilling key aspects of planning, organizing, and reporting. The active involvement of local government in the collection, distribution, and utilization of ZIS demonstrates that policy-based zakat management effectively fosters social awareness and contributes to the economic recovery of disaster-affected communities.Penelitian ini bertujuan untuk mengkaji mekanisme pengelolaan zakat, infaq, dan sadaqah (ZIS) oleh Lembaga Pemerintahan Nagari Sungai Pua dalam rangka pemulihan ekonomi masyarakat pasca bencana di Nagari Sungai Pua. Bencana alam yang terjadi di Nagari Sungai Pua diketahui telah menimbulkan kerugian yang siginifikan terhadap keberlangsungan ekonomi masyarakat. Sebagian besar korban bencana mengalami kehilangan tempat tinggal yang sekaligus sebagai tempat usaha, mata pencaharian, gagal panen, dan sebagainya. Kondisi ini mendorong Lembaga Pemerintahan Nagari Sungai Pua untuk secara kolektif mengatur mekanisme pengelolaan ZIS dengan kebijakan daerah yang relevan dengan kondisi sosial masyarakat. Penelitian ini merupakan penelitian lapangan. Data penelitian bersumber dari sumber primer, seperti wawancara dengan Lembaga Pemerintahan Nagari Sungai Pua, tokoh masyarakat, dan korban bencana. Hasil penelitian ini menunjukkan bahwa mekanisme pengelolaan ZIS di Nagari Sungai Pua dilakukan secara sistematis dengan indikasi terpenuhinya aspek perencanaan, pengorganisasian, dan pelaporan. Keterlibatan Lembaga Pemerintahan Nagari Sungai Pua dalam penghimpunan, penyaluran, dan pendayagunaan ZIS menunjukkan bahwa pengelolaan zakat berbasis kebijakan daerah telah membangun kepedulian sosial masyarakat setempat dalam memulihkan perekonomian masyarakat korban bencana alam.